A new species of Tenuipalpus sensu stricto (Acari: Tenuipalpidae) from Brazil, with ontogeny and a key to the known species - Castro, Elizeu B. [UNESP]; Feres, Reinaldo J.F. [UNESP]; Ochoa, Ronald; Bauchan, Gary R. (Magnolia Press, 2016)
The Cerrado is the second largest Brazilian biome, and is considered to be a hotspot due the great concentration of endemic species and high rate of deforestation. Surveys of the mite fauna present in this biome have revealed a great number of new species. In this paper, we describe Tenuipalpus spinosaurus sp. nov. (Acari: Tenuipalpidae), a new species of Tenuipalpus sensu stricto, from adult females, deutonymphs, protonymphs, larvae and eggs, collected on Terminalia argentea (Combretaceae), from the Cerrado in Brazil. Females of this new species bear a prominent longitudinal crest on the opisthosoma. The ontogenetic changes in the idiosoma and leg chaetotaxy of all stages are presented. A key to the world species of Tenuipalpus sensu stricto is provided.
Keywords: Biodiversity; Body projections; Cerrado; Crest; Flat mites; LT-SEM; Systematic; Taxonomic; Tenuipalpus spinosaurus